2014
DOI: 10.9790/487x-16637276
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Brand Name on Consumer Choice & Decision

Abstract: Brand image or Brand name plays a crucial role to enhance the performance of any company or business. Brand name is the tool which can positively change people's buying behavior. The purpose of this study is to examine the Effect of brand name on consumer buying behavior in University students of Gujranwala, Faisalabad and Lahore. Questionnaire survey was used to collect the data by using non probability convenient sampling technique. The researchers sent 300 questionnaires to the different university students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 8 publications
0
14
0
3
Order By: Relevance
“…The importance of brand name (BN) has been revealed in this study as it was found to positively and significantly influence consumer buying behaviour, with a coefficient value of 0.251 and significance level of 0.001. Previous study by Shehzad, Ahmad, Iqbal, Nawaz and Usman (2014) reveal that brand name has a significant positive relationship with consumer buying behaviour. The authors further argue that consumers are brand conscious and prefer branded products.…”
Section: Regression Analysismentioning
confidence: 91%
“…The importance of brand name (BN) has been revealed in this study as it was found to positively and significantly influence consumer buying behaviour, with a coefficient value of 0.251 and significance level of 0.001. Previous study by Shehzad, Ahmad, Iqbal, Nawaz and Usman (2014) reveal that brand name has a significant positive relationship with consumer buying behaviour. The authors further argue that consumers are brand conscious and prefer branded products.…”
Section: Regression Analysismentioning
confidence: 91%
“…Shehzad et al, [6] concluded that brand plays an important role to boost up the economy of any country. Brand is only tool that can change the buyer's behavior.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Hasil penelitian Shehzad et, al., (2014) di Pakistan, brand image berhubungan positip signifikan dengan perilaku membeli. Mahasiswa masuk ke universitas karena branding.…”
Section: Pendahuluanunclassified